الوصايا في النثر العربي وتوظيفها في تعليم القراءة لغير الناطقين بالعربية : المستوى المتقدم - بمبا، آدم (Kulliyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 1999)
This research aims at utilizing the art of wasaya (Advices) in Arabic literature as a tool for enhancing students' reading skills. The inductive, descriptive and critical methods have been adopted in studying the different styles of wasaya to determine the distinguishing properties of each of these styles. Three types of wasaya have been used in designing lessons for students. These are: a)The Islamic political wasaya as represented by Al - Hasan Al - Basri's wasiyah describing the qualities of Al - Imam Al - Adil or the just leader. b)The social wasaya in the Abbasid period as represented by "Abdallah b. AlMuqaffa's wasiyah in Sadaqah or friendship. c)The contemporary educational wasaya as represented by Ahmad Amin's wasiyah for his son. The most important properties that differentiate the art of wasaya from other prosaic arts are: a)wasiyah always starts with a vocative sentence (Nida'). b)wasiyah always conclude with an invocation (do 'a). The wasiyah can be used in a variety of fields, in religion, education, politics, and the like. This provides a wide range of choice to students to select the field based upon his/her interests.